SOX2 induces LPCAT1 expression to promote cholesterol metabolic reprogramming-mediated invasion and metastasis in osteosarcoma - Zhu, Linchao; Sun, Ying (Frontiers in Molecular Biosciences, 2025)
BackgroundSOX2 and LPCAT1 are implicated in tumor progression, but their roles in osteosarcoma pathogenesis and cholesterol metabolism remain unclear.MethodSOX2 and LPCAT1 expression in osteosarcoma tissues and cell lines was assessed via qRT-PCR and Western blot. Functional assays (CCK-8, wound healing and Transwell) evaluated proliferation, migration, and invasion of osteosarcoma cells. SOX2-LPCAT1 binding was confirmed by dual-luciferase reporter assay and ChIP assays. RNA sequencing and bioinformatics analyses explored cholesterol metabolism pathways. In vitro and in vivo models (xenograft tumor model and lung metastasis model) validated mechanistic roles.ResultSOX2 and LPCAT1 were overexpressed in osteosarcoma. LPCAT1 or SOX2 overexpression promoted malignant behaviors and cholesterol metabolism (free cholesterol/total cholesterol levels, SREBP1/INSIG1 expression) of osteosarcoma cells, while shSOX2 or shLPCAT1 did the opposite. SOX2 transcriptionally activated LPCAT1. LPCAT1 reversed shSOX2-induced suppression, while LPCAT1 knockdown attenuated SOX2-driven oncogenicity. In vivo, LPCAT1 enhanced tumor growth, lung metastasis, and cholesterol metabolism, while these effects were counteracted by SOX2 inhibition.ConclusionThe SOX2/LPCAT1 axis drives osteosarcoma progression by modulating cholesterol metabolism.